Recurrent Multifocal Mycoplasma orale Infection in an Immunocompromised Patient: A Case Report and Review. (10th August 2020) - Ketchersid, Jeffrey; Scott, Jake; Lew, Thomas; Banaei, Niaz; Kappagoda, Shanthi
Abstract : A young woman with mixed connective tissue disease complicated by erosive arthritis, secondary hypogammaglobulinemia due to rituximab, and a history of many infectious complications developed multiple nonhealing wounds, polyarticular joint pain, and leukocytosis. Radiographic studies demonstrated multiple scattered areas of osteomyelitis and complex abscesses. Purulent fluid drained from multiple sites did not yield a microbiologic diagnosis by standard culture technique, but Mycoplasma orale was ultimately identified using 16 S ribosomal RNA gene amplification and sequencing. We describe this unique case and review the literature.